Challenges to create an evidence-based programme register in France. (13th November 2019) - Arwidson, P; Verry-Jolive, C
Abstract: The majority of health promotion and disease prevention interventions implemented in both targeted and general populations have unknown effectiveness. This contrasts with drug treatments which must be proven effective before they can be prescribed. The recent evaluation of four addiction prevention interventions chosen by public health implementers showed that two had positive impacts on addiction prevention and two had deleterious effects. Despite over 50 years' worth of scientific literature on the evaluation of health promotion and disease prevention programmes, it is little known and little used by project promoters. These promoters cannot be blamed for not using this literature as it is often difficult to access, to read and to understand. Even if they successfully access and read the articles, interventions are often not described properly, rendering the text useless for implementers. It is therefore necessary to create interfaces that translate this literature into a form useful for funders and project promoters. As a result, Public Health France has studied existing portals in both the United States and in Europe. An independent double-reviewing process comparable to the review process used by scientific journals for manuscripts as in the Norwegian portal was chosen for this reason.An expert committee has worked during more than one year to design and test a scoring grid that will be published soon. The 80+ programme evaluations found in the scientific literature will now be reviewed with the approved grid. Public Health France has also begun visiting each region in France to present the portal to local health authorities and NGOs to enable project promoters to submit their programmes soon and to promote the use of evidence-based or research-based programmes when possible.